2015
DOI: 10.4103/0974-777x.154444
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile of neonatal septicemia in a tertiary care hospital from Western India

Abstract: Neonatal septicemia is an important cause of morbidity and mortality. The present study was undertaken to determine the bacteriological profile and antimicrobial susceptibility pattern of prevalent pathogens isolated from the blood of septicemic neonates from Neonatal Intensive Care Unit (NICU). A total of 180 blood samples of septicemic neonates were studied bacteriologically. Antimicrobial susceptibility testing was done by the Kirby Bauer disc diffusion method in accordance to Clinical Laboratory Standards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
50
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 11 publications
27
50
3
Order By: Relevance
“…This result is inconstant with many previous results [17]- [19] that reported Staphylococci as the most common cause of neonatal sepsis. However, many studies agreed with our result [20] [21]. This may be due to environmental differences and differences in the supportive care and infection control practices between different centers.…”
Section: Discussionsupporting
confidence: 81%
“…This result is inconstant with many previous results [17]- [19] that reported Staphylococci as the most common cause of neonatal sepsis. However, many studies agreed with our result [20] [21]. This may be due to environmental differences and differences in the supportive care and infection control practices between different centers.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings were in accordance with Peterside O et al and Muley VA et al, who found EONS in 66% and 66.7% cases respectively and LONS in 34% and 33.3% cases respectively. 17, 18 Jyothi P et al found EONS (74.8%) three times higher than LONS (25.2%). 14 The clustering of these almost 2/3 rd cases within 72 hours of life reflects the immaturity of immunological responses in newborn.…”
Section: Age Wise Distribution Of Casesmentioning
confidence: 99%
“…14 The clustering of these almost 2/3 rd cases within 72 hours of life reflects the immaturity of immunological responses in newborn. 18 The EONS occurs due to ascending infection from infected birth canal or following rupture of membrane usually caused by Gram-negative organisms acquired after birth from human contact. In the present study, mothers of 31.71% neonates had history of prolonged rupture of membrane.…”
Section: Age Wise Distribution Of Casesmentioning
confidence: 99%
“…However, other studies have documented culture positivity rate of 26.6-46.2%. 8,14 A high rate of culture positives may be due to the fact that screening for sepsis was done in all high-risk neonates as well as those with clinical features suggestive of sepsis. It has been documented that up to 26% cases of neonatal sepsis may be caused by anaerobes.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Studies from the Indian subcontinent have demonstrated different causative organisms as compared to Western studies. [6][7][8] There are large number of studies across the India to establish cause of neonatal infections. However, there was a large number of patients with neonatal sepsis were being admitted to the neonatal intensive care unit (NICU) of our institute.…”
Section: Introductionmentioning
confidence: 99%